AUTHORITY OF THE STATE ADMINISTRATIVE JURISDICTION TO CONSIDER ELEMENTS OF AUTHORITY ABUSE RELATED TO THE CRIME OF CORRUPTION - Susilo Handoyo; Ratna Lutfitasari (JURNAL DARMA AGUNG, 2023)
The objective of this study is to examine, understand, and analyze the logic of Article 21 paragraph (1) of Law No. 30 of 2014 concerning Government Administration, which empowers the State Administrative court to look into instances of abuse of power, as well as the ramifications of PTUN's authority to look into abuse of power in the prosecution of corrupt acts. This study used normative legal research, which involved using library research to conduct searches for legal sources.